Höchstfeste Multimaterialsysteme aus Stahl und Faserverbundkunststoffen - Lauter, Christian; Tröster, Thomas; Sköck-Hartmann, Britta; Gries, Thomas; Linke, Marcus (VDI Konstruktion: Ingenieur-Werkstoffe)

GARLig: A fully automated tool for subset selection of large fragment spaces via a self-adaptive genetic algorithm - Pfeffer, P.; Fober, T.; Hüllermeier, Eyke; Klebe, G. (Journal of Chemical Information and Modeling)

Combining predictions in pairwise classification: An optimal adaptive voting strategy and its relation to weighted voting - Hüllermeier, Eyke; Vanderlooy, S. (Pattern Recognition)

On predictive accuracy and risk minimization in pairwise label ranking - Hüllermeier, Eyke; Fürnkranz, J. (Journal of Computer and System Sciences)

Europarecht inklusive CD-ROM mit Gesetzen, Urteilen, Hörfassung und interaktiven Falllösungen - Krimphove, Dieter

Handelsrecht - mit Grundzügen des Wechsel- und Scheckrechts (Gesetze, Urteile, Fälle und Lösungen, Sprachfassung auf interaktiver CD) - Krimphove, Dieter

A Continuous, Local Strategy for Constructing a Short Chain of Mobile Robots - Degener, Bastian; Kempkes, Barbara; Kling, Peter; Meyer auf der Heide, Friedhelm (Structural Information and Communication Complexity)

A local O(n2) gathering algorithm - Degener, Bastian; Kempkes, Barbara; Meyer auf der Heide, Friedhelm (Proceedings of the 22nd ACM symposium on Parallelism in algorithms and architectures - SPAA '10)

Automata, Languages and Programming, 37th International Colloquium, ICALP 2010, Bordeaux, France, July 6-10, 2010, Proceedings, Part II.

Automata, Languages and Programming, 37th International Colloquium, ICALP 2010, Bordeaux, France, July 6-10, 2010, Proceedings, Part I.

Evaluation of cost functions for FEA based transducer optimization - Schröder, Andreas; Rautenberg, Jens; Henning, Bernd (Physics Procedia)

A new method of spatial filtering for Schlieren visualization of ultrasound wave fields - Unverzagt, Carsten; Olfert, Sergei; Henning, Bernd (Physics Procedia)

PC gestützte Entwicklung von Ultraschallsensoren - Henning, Bernd

Adaptives Mode-Tracing und numerische Stabilisierung modellierter Anregungsstrukturen für die halbanalytische Simulation geführter Wellen - Bause, Fabian; Henning, Bernd

Halbanalytische Modellierung akustischer Wellenausbreitung im ein- und mehrschichtigen Wellenleiter - Bause, Fabian

Effizientes Ultraschalltransducerdesign und Methoden zur akustischen Materialdatenbestimmung - Henning, Bernd

Ausbeute und Fehlertoleranz bei dreifach modularer Redundanz - Hunger, Marc; Hellebrand, Sybille (4. GMM/GI/ITG-Fachtagung "Zuverlässigkeit und Entwurf")

Nano-Electronic Systems - Hellebrand, Sybille

Nucleate pool boiling, film boiling and single-phase free convection at pressures up to the critical state. Part II: Circumferential variation of the wall superheat for a horizontal 25mm copper cylinder - Gorenflo, Dieter; Baumhögger, Elmar; Windmann, Thorsten; Herres, Gerhard (International Journal of Refrigeration)

Nucleate pool boiling, film boiling and single-phase free convection at pressures up to the critical state. Part I: Integral heat transfer for horizontal copper cylinders - Gorenflo, Dieter; Baumhögger, Elmar; Windmann, Thorsten; Herres, Gerhard (International Journal of Refrigeration)

The Use of Instant Messaging in Working Relationship Development: A Case Study - Cho, Hee-Kyung; Trier, Matthias; Kim, Eunhee (Journal of Computer-Mediated Communication)

Struktur und Dynamik in der Netzwerkanalyse - Trier, Matthias (Handbuch Netzwerkforschung)

Towards a Systematic Approach for Capturing Knowledge-Intensive Business Processes - Trier, Matthias; Müller, Claudia (Practical Aspects of Knowledge Management)

Analyzing the Dynamics of Community Formation Using Brokering Activities - Trier, Matthias; Bobrik, Annette (Communities and Technologies 2007)

Network coding in passive optical networks - Miller, Konstantin; Biermann, Thorsten; Woesner, Hagen; Karl, Holger (Network Coding (NetCod), 2010 IEEE International Symposium on)

Tutte's 5-flow conjecture for cyclically highly connected cubic graphs - Steffen, Eckhard (Discrete Mathematics)

Bricks and conjectures of Berge, Fulkerson and Seymour - Mkrtchyan, Vahan; Steffen, Eckhard (arXiv:1003.5782)
An $r$-graph is an $r$-regular graph where every odd set of vertices is connected by at least $r$ edges to the rest of the graph. Seymour conjectured that any $r$-graph is $r+1$-edge-colorable, and also that any $r$-graph contains $2r$ perfect matchings such that each edge belongs to two of them. We show that the minimum counter-example to either of these conjectures is a brick. Furthermore we disprove a variant of a conjecture of Fan, Raspaud.

RiaS: overlay topology creation on a PlanetLab infrastructure - Lischka, Jens; Karl, Holger (Proceedings of the second ACM SIGCOMM workshop on Virtualized infrastructure systems and architectures)

Energy efficiency model of network-coded cooperation in wireless sensor networks - Woldegebreal, Dereje H; Karl, Holger (Sensor Technologies and Applications (SENSORCOMM), 2010 Fourth International Conference on)

Cooperative communication to improve reliability and efficient neighborhood wakeup in wireless sensor networks - Khan, Rana Azeem M; Karl, Holger (Proceedings of the Fourth International Conference on Mobile Ubiquitous Computing (UBICOMM 2010))

Do we know the band gap of lithium niobate? - Thierfelder, Christian; Sanna, Simone; Schindlmayr, Arno; Schmidt, Wolf Gero (Physica Status Solidi C)
Given the vast range of lithium niobate (LiNbO3) applications, the knowledge about its electronic and optical properties is surprisingly limited. The direct band gap of 3.7 eV for the ferroelectric phase – frequently cited in the literature – is concluded from optical experiments. Recent theoretical investigations show that the electronic band‐structure and optical properties are very sensitive to quasiparticle and electron‐hole attraction effects, which were included using the GW approximation for the electron self‐energy and the Bethe‐Salpeter equation respectively, both based on a model screening function. The calculated fundamental gap was found to be at least 1 eV larger than the experimental value. To resolve this discrepancy we performed first‐principles GW calculations for lithium niobate using the full‐potential linearized augmented plane‐wave (FLAPW) method. Thereby we use the parameter‐free random phase approximation for a realistic description of the nonlocal and energydependent screening. This leads to a band gap of about 4.7 (4.2) eV for ferro(para)‐electric lithium niobate.

Ab initiog-tensor calculation for paramagnetic surface states: hydrogen adsorption at Si surfaces - Gerstmann, Uwe; Rohrmüller, M.; Mauri, F.; Schmidt, Wolf Gero (physica status solidi (c))

Optical anisotropy of Si(111)-(4 × 1)/(8 × 2)-In nanowires calculated fromfirst-principles - Wippermann, S.; Schmidt, Wolf Gero; Bechstedt, F.; Chandola, S.; Hinrichs, K.; Gensch, M.; Esser, N.; Fleischer, K.; McGilp, J. F. (physica status solidi (c))

Bayes optimal multilabel classification via probalistic classifier chains - Dembczynski, K.; Cheng, W.; Hüllermeier, Eyke (in Proceedings ICML-2010, 27th International Conference on Machine Learning, Haifa, Israel)

Label ranking based on the Plackett-Luce model - Cheng, W.; Dembczynski, K.; Hüllermeier, Eyke (in Proceedings ICML-2010, 27th International Conference on Machine Learning, Haifa, Israel)

Graded multi-label classification: The ordinal case - Cheng, W.; Dembczynski, K.; Hüllermeier, Eyke (in Proceedings ICML-2010, 27th International Conference on Machine Learning, Haifa, Israel)

Regret analysis for performance metrics in multi-label classification: The case of Hamming and subset zero-one loss - Dembczynski, K.; Waegeman, W.; Cheng, W.; Hüllermeier, Eyke (In Proceedings ECML/PKDD-2010, European Conference on Machine Learning and Principles and Practice of Knowledge Discovery in Databases, ,Bareclona, Spain)

Predicting partial orders: Ranking with abstention - Cheng, W.; Rademaker, M.; De Beats, B.; Hüllermeier, Eyke (In Proceedings ECML/PKDD-2010, European Conference on Machine Learning and Principles and Practice of Knowledge Discovery in Databases, ,Bareclona, Spain)

Uncertainty in clustering and classification - Hüllermeier, Eyke (in Proceedings SUM 2010, International Conference on Scalable Uncertainty Management)

A Triple Hybrid Interconnect for Many-Cores: Reconfigurable Mesh, NoC and Barrier - Giefers, Heiner; Platzner, Marco (Proceedings of the 20th International Conference on Field Programmable Logic and Applications (FPL))

Engineering Self-Coordinating Software Intensive Systems - Schäfer, Wilhelm; Birattari, Mauro; Blömer, Johannes; Dorigo, Marco; Engels, Gregor; O'Grady, Rehan; Platzner, Marco; Rammig, Franz-Josef; Reif, Wolfgang; Trächtler, Ansgar (Proceedings of the Foundations of Software Engineering (FSE) and NITR & D/SPD Working Conference on the Future of Software Engineering Research (FoSER))

A Self-Reconfigurable Lightweight Interconnect for Scalable Processor Fabrics - Giefers, Heiner; Platzner, Marco (Proceedings of the 10th International Conference on Engineering of Reconfigurable Systems and Algorithms (ERSA))

Manganese-hydrogen complexes inGa1−xMnxN - Bihler, C.; Gerstmann, Uwe; Hoeb, M.; Graf, T.; Gjukic, M.; Schmidt, Wolf Gero; Stutzmann, M.; Brandt, M. S. (Physical Review B)

Catalytic Action of a Cu(111) Surface on Tetraazaperopyrene Polymerization - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry Letters)

Entropy Explains Metal-Insulator Transition of the Si(111)-In Nanowire Array - Wippermann, S.; Schmidt, Wolf Gero (Physical Review Letters)

Defects in carbon implanted silicon calculated by classical potentials and first-principles methods - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, J. K. N.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

First-principles investigation of CO adsorption on Pt/Ge(001)-(4×2) - Krivosheeva, A.V.; Sanna, S.; Schmidt, Wolf Gero (Computational Materials Science)

Understanding the cubic AlN growth plane from first principles - Rauls, E.; Wiebe, J.; Schmidt, Wolf Gero (Journal of Crystal Growth)

Metal-insulator transition in Si(111)-(4 × 1)/(8 × 2)-In studied by optical spectroscopy - Speiser, E.; Chandola, S.; Hinrichs, K.; Gensch, M.; Cobet, C.; Wippermann, S.; Schmidt, Wolf Gero; Bechstedt, F.; Richter, W.; Fleischer, K.; McGilp, J. F.; Esser, N. (physica status solidi (b))

First-principles study of water adsorption and a high-density interfacial ice structure on(1×1)-O/Rh(111) - Thierfelder, C.; Schmidt, Wolf Gero (Physical Review B)

Lithium niobateX-cut,Y-cut, andZ-cut surfaces fromab initiotheory - Sanna, Simone; Schmidt, Wolf Gero (Physical Review B)

GaN/LiNbO3 (0001) interface formation calculated from first-principles - Sanna, Simone; Schmidt, Wolf Gero (Applied Surface Science)

Magnetic characterization of conductance electrons in GaN - Scholle, A.; Greulich-Weber, S.; As, Donat Josef; Mietze, Ch.; Son, N. T.; Hemmingsson, C.; Monemar, B.; Janzén, E.; Gerstmann, Uwe; Sanna, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (b))

Chemical reactivity on surfaces: Modeling the imide synthesis from DATP and PTCDA on Au(111) - Rauls, E.; Blankenburg, S.; Schmidt, Wolf Gero (Physical Review B)

Fine Structure of Triplet Centers in Room Temperature Irradiated 6H-SiC - Scholle, Andreas; Greulich-Weber, Siegmund; Rauls, Eva; Schmidt, Wolf Gero; Gerstmann, Uwe (Materials Science Forum)
In non-annealed 6H-SiC samples that were electron irradiated at room temperature, a new EPR signal due to a S=1 defect center with exceptionally large zero-field splitting (D = +652•10-4 cm-1) has been observed under illumination. A positive sign of D demonstrates that the spin-orbit contribution to the zero-field splitting exceeds by far that of the spin-spin interaction. A principal axis of the fine structure tilted by 59° against the crystal c-axis as well as the exceptionally high zero-field splitting D can be qualitatively understood by the occurrence of additional close-lying defect levels in defect clusters resulting in comparatively large second-order spin-orbit coup¬ling. A tentative assignment to vacancy clusters is supported by the observed annealing behavior.

GaN growth on LiNbO3 (0001) - a first-principles simulation - Sanna, Simone; Schmidt, Wolf Gero (physica status solidi (c))

Temperature dependent stability of self-assembled molecular rows - Blankenburg, S.; Schmidt, Wolf Gero (physica status solidi (c))

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))

Ab initio investigation of the LiNbO3(0001) surface - Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (physica status solidi (c))

Dissociative and molecular adsorption of water onα-Al2O3(0001) - Wippermann, S.; Schmidt, Wolf Gero; Thissen, P.; Grundmeier, G. (physica status solidi (c))

Aus dem Deutschen ins Italienische (zusammen mit M. Brusotti, L. Gasperoni und C. Piazzesi): G. Abel, Filosofia dei segni e dell’interpretazione

Nuzzo, Angelica (Ed.), Hegel and the Analytic Tradition, London/New York 2010 - Ficara, Elena (Hegel-Studien)

Negation und die Logik der Philosophie bei Hegel - Ficara, Elena (Nichts, Negation, Nihilismus. Die Europäische Moderne als Erkenntnis und Erfahrung des Nichts)

Due in uno. Che cosa è e che cosa fa l’io che pensa - Ficara, Elena (Filosofia dell’avvenire)

Der ontologische Gottesbeweis bei Hegel und in der Analytischen Philosophie - Ficara, Elena (Gott in der deutschen klassischen Philosophie und im Denken der Gegenwart)

Ursprünge des Ausdrucks ’das Logische’ beim frühen Hegel - Ficara, Elena (Archiv für Begriffsgeschichte)

Immagini della dialettica hegeliana. La croce e la rosa. - Ficara, Elena (Archivio di storia della cultura)

Hegel’s Dialectic in Contemporary Philosophy - Ficara, Elena (Idealistic Studies)

Heidegger e il problema della metafisica - Ficara, Elena

Scalable Multi Phase Interleaved Boundary Mode PFC Concept enabling Energy- and Cost Efficient PSUs in the kW-Range - Schafmeister, Frank; Wang, Xudong; Grote, Tobias; Ide, Peter (Proc. IEEE International Symposium on Industrial Electronics (ISIE))

FPGA-based realization of self-optimizing drive-controllers - Paiz, C.; Hagemeyer, J.; Pohl, C.; Porrmann, M.; Rückert, U.; Schulz, B.; Peters, W.; Böcker, Joachim (2009 35th Annual Conference of IEEE Industrial Electronics)

Optimal energy management for a hybrid energy storage system for electric vehicles based on Stochastic Dynamic Programming - Romaus, Christoph; Gathmann, Kai; Böcker, Joachim (2010 IEEE Vehicle Power and Propulsion Conference)

Efficiency improvement of an IPMSM using Maximum Efficiency operating strategy - Pohlenz, Daniel; Böcker, Joachim (Proceedings of 14th International Power Electronics and Motion Control Conference EPE-PEMC 2010)

Observer for the rotor temperature of IPMSM - Specht, Andreas; Böcker, Joachim (Proceedings of 14th International Power Electronics and Motion Control Conference EPE-PEMC 2010)

Multiobjective search for the management of a hybrid energy storage system - Boxnick, Simon; Klopfer, Stefan; Romaus, Christoph; Klopper, Benjamin (2010 8th IEEE International Conference on Industrial Informatics)

Energy transfer with doubly-excited switched reluctance drive - Schneider, T.; Schulte, C.; Mathapati, S.; Böcker, Joachim (SPEEDAM 2010)

Modeling and Control Design for a Very Low-Frequency High-Voltage Test System - Cao, Z.; Hu, M.; Fröhleke, N.; Böcker, Joachim (IEEE TRANSACTIONS ON POWER ELECTRONICS 25(2))

Optimal Design of Motor and Gear for Drives With High Acceleration by Consideration of Torque–Speed and Torque–Acceleration Product - Grotstollen, Horst (IEEE Transactions on Industry Applications)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Control and Systems Engineering

The Ariadne System. A flexible and extensible framework for the modeling and storage of experimental data in the humanities - Menke, Peter; Mehler, Alexander (Proceedings of LREC 2010)

Towards a Simulation Model of Dialogical Alignment - Mehler, Alexander; Weiß, Petra; Menke, Peter; Lücking, Andy (Proceedings of the 8th International Conference on the Evolution of Language (Evolang8))

Rudolf Seising, The Fuzzification of Systems. The Genesis of Fuzzy Set Theory and Its Initial Developments up to the 1970s. Springer: Berlin/Heidelberg 2007 (Studies in Fuzziness and Soft Computing; 216) - Peckhaus, Volker (Isis)

FDM Part Quality Manufactured with ULTEM 9085 - Bagsik, A.; Schöppner, Volker; Klemp, E. (Proceedings of International Conference Polymeric Materials)
Generative production techniques have the advantage of manufacturing parts via an additive process without needing a forming tool. One of these additive manufacturing technologies is “Fused Deposition Modeling” (FDM). From a 3D-CAD data set, components and assemblies are manufactured out of thermoplastic material in only a few working steps. Native software automatically slices the data, calculates the support structures, and creates toolpaths. The parts then are built up layer by layer by means of an additive process. An extrusion head deposits the molten thermoplastic filament to create each layer. This technology began as a process for creating prototype parts; recently it has found new utility in the production of manufacturing tools and as a manufacturing process for end-use parts. In order to be used as a part for serial production, the components must possess the required mechanical properties. To this end, not only is the chosen material relevant, but a correct process control is also necessary. An interesting material for the aircraft and automotive industry is the material PEI with the trade name Ultem*9085. This material should typically be used on FDM-machines for the manufacturing of end products. The aim of the research is to determine the present mechanical data based on the process control, as well as reproducibility from job to job. In this work the influence of the orientation and the structure of the manufactured parts based on the mechanical data are analyzed. Sample parts are generated with the given parameters of the native software based upon the CAD data. First, specimens were analyzed concerning their geometry and configuration. The dimensions and weight were measured. The mechanical tests conducted were the tensile and compression tests.

Robert und Hermann Grassmann’s Influence on the History of Formal Logic (Videomitschnitt des Vortrags) - Peckhaus, Volker (International Grassmann Conference. Hermann Grassmann Bicentennial: Potsdam and Szczecin, 16–19 September 2009. Video Recording of the Conference)

Entwurf und Betrieb hybrid-elektrischer Fahrzeugantriebe am Beispiel von Abfallsammelfahrzeugen - Knoke, T.

Wirkungsgradoptimierte Regelung hoch ausgenutzter Permanent-Synchronmaschinen im Antriebsstrang von Automobilen - Meyer, M.

Power Supplies for High-Power Piezoelectric Ultrasonic Motor - Li, R.

Hochschulforscher oder Hochschullehrer? Eine Panel-Daten-Analyse wirtschaftswissenschaftlicher Bachelor- und Masterkurse - Lück, Sonja (Hochschulmanagement)

Portfolioarbeit im fremdsprachlichen Schreibunterricht - Ballweg, Sandra (Grenzen überschreiten: sprachlich – fachlich – kulturell. Dokumentation zum 23. Kongress für Fremdsprachendidaktik der Deutschen Gesellschaft für Fremdsprachenforschung (DGFF). Leipzig, 30. September – 3. Oktober 2009)

Kommunikation und Interaktion in pädagogischen Kontexten – berufs- und wirtschaftspädagogische Perspektiven - Buer, Jürgen van; Niederhaus, Constanze (Handbuch Berufs- und Wirtschaftspädagogik)

Fachtexte in der Berufsausbildung. Ein linguistischer Vergleich von Texten aus Fachkundebüchern für die Berufsfelder Körperpflege und Elektrotechnik - Niederhaus, Constanze (Die berufsbildende Schule (62))

AlphaZ Evaluation. Sachbericht 2009 - Badel, Steffi; Niederhaus, Constanze

Basis Deutsch. Kopiervorlagen für die Berufsvorbereitung mit CD-ROM - Köhler-Knacker, Margitta; Niederhaus, Constanze; Nowak, Klaus; Wenzke, Anselm

Gezielt fördern. Verben, Präpositionen, Satzglieder, Sätze. Arbeitsheft 7./8 - Müller, Julia; Niederhaus, Constanze; Robben, Christiane

Almog, Joseph, “Frege’s Puzzles”, In: Journal of Philosophical Logic 37 (2008), 549–574 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Philosophische Tagebücher 1803–1810. Zweiter Teil", hg. v. Jan Berg (Bernard Bolzano-Gesamtausgabe. Reihe II. B.15), Friedrich Frommann Verlag-Günther Holzboog: Stuttgart-Bad Cannstatt 2009 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Philosophische Tagebücher 1803–1810. Erster Teil", hg. v. Jan Berg (Bernard Bolzano-Gesamtausgabe. Reihe II. B.14), Friedrich Frommann Verlag-Günther Holzboog: Stuttgart-Bad Cannstatt 2009 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

De Risi, Vincenzo, "Geometry and Monadology. Leibniz’s Analysis Situs and Philosophy of Space", Birkhäuser: Basel/Boston/Berlin 2007 (Science Networks. Historical Studies; 33) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Degen, J.W., “Variations of Frege’s Grundgesetze”, In: Travaux de logique 18 (2007), 15–31 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Yearbook of Phraseology. Hg. von Koenraad Kuiper et al (Rezensiert von Häcker, Martina) - Ptashnyk, Stefaniya

Variation und die historische Sprachkontaktforschung: Am Beispiel der multilingualen Stadt Lemberg - Ptashnyk, Stefaniya (“Variatio delectat”. Empirische Evidenzen und theoretische Passungen sprachlicher Variation. Festschrift für Klaus J. Mattheier zum 65. Geburtstag)